Meningkatkan Minat Membaca Pada Anak Usia Sekolah Dasar Melalui Program Tayangan Televisi Dalam Perspektif Sosiologi - Bakhtiyar, Bakhtiyar; Hidayah, Imas Rahmadhtul (Trapsila: Jurnal Pendidikan Dasar, 2020)
The study aims to describe (1). The role of parents fostering interest in reading elementary school age children through television programs. (2). The positive impact of the TV program "Tau Gak Sih" on the development of reading interest in elementary school age children. The research is objecting to a comprehensive detailed study of the main content, the role of parents in assisting watching television programs to foster interest in reading. The scope of the study includes analysis-based analysis activities, focusing on the role of managing elementary school children's interest in reading by assisting learning. Analysis requires realistic critical thinking to apply conceptualization, so that it uses a historical approach characterized by realistic critical inquiry into the development of a thought. Primary information sources are used as primary data. The technique of collecting data utilizes library research, which is reading various kinds of literature. The analysis was conducted descriptively qualitative, sourced from theoretical reading material, research and not research. The validity of the research can be achieved by utilizing content analysis, in order to analyze the meaning, the role of parents, the function of the family in developing interest in reading elementary school-age children through TV programs. Observation is used as an element to support the construction of the theory. The results of the study include; (1) Parents play an important role in providing assistance in fostering elementary school-age children's interest in reading through television programs. (2) The positive impact of the TV program "Tau Gak Sih" on the development of reading interest in elementary school age children is as a medium of learning, expanding knowledge and motivating reading activities